KNOWLEDGE AMONG PATIENT ABOUT THE MODIFIABLE RISK FACTORS OF HEART DISEASE (International Journal of Food and Nutritional Sciences, 2022)
Knowledge is an important pre-requisite for implementing both primary as well as secondary preventive strategies for heart disease. The present study was conducted with an objective to find out the type of heart disease present among the patients, to know the knowledge of patients regarding relationship between obesity, smoking and heart disease. To know the patients beliefs about exercise and heart disease. A comprehensive questionnaire-cum-interview schedule was designed to collect the desired information. A total no. of 50 patients of both the sexes suffering from Heart Disease were selected. The sample was collected from Outpatient Department (OPD) of cardiology of SMHS and SKIMS hospital of District Srinagar Kashmir. The two scales were used in questionnaire i.e. ordinal and likert scale. Sample was selected by simple random purposive sampling technique. The results of the study revealed that majority of respondents were having angina pectoris. Majority of male as well as female respondents i.e. 65.7% and 60% respectively were having knowledge about relationship between smoking and heart disease. They were of the opinion that smoking increases the risk of heart disease. Majority of male as well as female respondents i.e. 80% respectively were having knowledge about relationship between obesity and heart disease. They were of the opinion that obesity increases the risk of heart disease.Majority of male as well as female respondents i.e. 57.1% and 53.3% respectively agreed to the statement that regular exercise can lower their risk of developing heart disease.